Analytical Review: A Guide to Evaluating Financial Statements (Book). - Hendrickson, Harvey S.; Heintz, James A. (The Accounting Review, 1985)
Reviews the book "Analytical Review: A Guide to Evaluating Financial Statements," by Edward Blocher and John J. Willingham.